Is it really a neuromyth? A meta-analysis of the learning styles matching hypothesis - Clinton-Lisell, Virginia; Litzinger, Christine (Frontiers in Psychology, 2024)
Learning styles have been a contentious topic in education for years. The purpose of this study was to conduct a meta-analysis of the effects of matching instruction to modality learning styles compared to unmatched instruction on learning outcomes. A systematic search of the research findings yielded 21 eligible studies with 101 effect sizes and 1,712 participants for the meta-analysis. Based on robust variance estimation, there was an overall benefit of matching instruction to learning styles, g = 0.31, SE = 0.12, 95% CI = [0.05, 0.57], p = .02. However, only 26% of learning outcome measures indicated matched instruction benefits for at least two styles indicating of a crossover interaction supportive of the matching hypothesis. Twelve studies without sufficient statistical details for the meta-analysis were also examined for indication of a crossover effect; 25% of these studies had findings indicative of a crossover interaction. Given the time and financial expenses of implementation coupled with low study quality, the benefits of matching instruction to learning styles are interpreted as too small and too infrequent to warrant widespread adoption.